Pembelajaran Bahasa Inggris Melalui Media Game Pada Anak Di Daerah Kota Padang Sidempuan - Aulia Ahmad Harahap; Mia Aulina Lubis (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Community service as an embodiment of one of the Tri Dharma of Higher Education carried out by Students of the Social Welfare Study Program, Faculty of Social and Political Sciences, University of North Sumatra through Practicum I at the Social Service of Padang Sidempuan City, which is located at Jl. Jendral Abdul Harris Nasution, No. 77 Pal IV Pijorkolong, Kec. North Padang Sidempuan , Padangsidimpuan City, North Sumatra. The development of technology at this time is very rapid, educational games are gradually being used as a learning tool in the world of education and can be used as a benchmark for producing more effective and efficient learning methods. Learning English for teenagers through playing games is an effective method for learning languages. The objectives of learning English through this game media include (1) increasing the enthusiasm of students to learn English. (2) improve the basic English skills of teenagers through effective, creative and interesting study learning.